Pengaruh Kualitas Produk, Harga, Kemasan Dan Legalitas Produk (PIRT) Terhadap Keputusan Pembelian Konsumen UMKM “Srikandi” KOTA BATU (Study Kasus Pada Desa Gondorejo Kecamatan Batu Kota Batu) - Bayu Antiko; Nur Hidayati; Muhammad Ridwan Basalamah (UNIVERSITAS ISLAM MALANG, 2021)
Abstract The purpose of this study is to determine and analyze product quality, price, packaging and legality of PIRT products that have a simultaneous effect on purchasing decisions for Srikandi SMEs in Batu City. To determine the effect of product quality on consumer purchasing decisions of Srikandi SMEs in Batu City. To determine the effect of price on consumer purchasing decisions of Srikandi SMEs in Batu City. To determine the effect of packaging on consumer purchasing decisions of Srikandi SMEs in Batu City. To determine the effect of the legality of PIRT products on the purchasing decisions of Srikandi UMKM consumers in Batu City.The population in this study amounted to 100 respondents and the samples taken were 50 respondents. Collecting data through the distribution of questionnaires. Data analysis in this study used SPSS Version 16. The sampling technique used quantitative methods and the data testing techniques used were Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Test and Hypothesis Testing.The results of the analysis show that Product Quality, Price, Packaging and Legality of PIRT Products simultaneously have an influence on the Consumer Purchase Decision of Srikandi MSMEs in Batu City. Partially Product Quality, Price and Packaging affect the purchasing decisions of Srikandi SMEs consumers. However, partially the legality of PIRT products has no effect on purchasing decisions for Srikandi MSMEs in Batu City. Keywords: Product Quality, Price, Packaging and Legality of PIRT Products on purchasing decisions.